Genome Sequence of a Porcine Extraintestinal Pathogenic Escherichia coli Strain - Tan, Chen (American Society for Microbiology, 2011)

(untitled)
Extraintestinal pathogenic Escherichia coli (ExPEC) is an important pathogen which can infect humans and animals and cause many diseases outside the intestine. Here, we report the first draft genome sequence of a porcine ExPEC strain, PCN033, isolated from a pig with meningitis.